2009
DOI: 10.1159/000260229
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Imaging of Cystoid Macular Edema in Diabetic Retinopathy

Abstract: Aim: Our purpose was to assess fundus autofluorescence (FAF) images in patients with diabetic retinopathy and cystoid macular edema (CME) and their correlation with fluorescein angiography (FA) and optical coherence tomography (OCT) findings. Methods: Sixty-eight eyes of 34 consecutive patients with diabetic retinopathy were examined with autofluorescence imaging using a confocal scanning laser ophthalmoscope, FA and OCT. The eyes were divided into 2 groups, group 1 with CME and group 2 without. Results: In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 18 publications
2
54
1
10
Order By: Relevance
“…11,12,14,31 The areas of autofluorescent cystoid spaces at the fovea were reported to be related to visual impairment, retinal thickness, and photoreceptor damage. 14 Vujosevic et al 12 reported that eyes with the multiple-spot type of autofluorescent cystoid spaces had poorer VA than those with the single-spot type.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,14,31 The areas of autofluorescent cystoid spaces at the fovea were reported to be related to visual impairment, retinal thickness, and photoreceptor damage. 14 Vujosevic et al 12 reported that eyes with the multiple-spot type of autofluorescent cystoid spaces had poorer VA than those with the single-spot type.…”
Section: Discussionmentioning
confidence: 99%
“…Sekiryu et al 19 reported that autofluorescence generated by the RPE cells travels through the sensory retina, and the intensity of the FAF changes according to the status of the overlying retina. Pece et al 20 reported that increased FAF during CME in patients with diabetes was not abnormal FAF, but instead, was the normal fluorescence of the RPE as observed through a defect in the xanthophyll pigment. However, they also reported that the visual acuity of patients with diabetic macular edema with increased FAF was worse than that of patients without increased FAF.…”
Section: Discussionmentioning
confidence: 99%
“…13 Fundus autofluorescence (FAF) imaging using a confocal scanning laser ophthalmoscope (cSLO) allows for topographic assessment of macular pathology with high resolution. Pece et al 14 found that conventional FAF imaging with a wavelength of 488 nm provides a sensitive, rapid and non-invasive way of assessing DMO, correlating well with FA and findings on OCT imaging. Vujosevic and colleagues 15 also described good correlation between FAF, OCT, FA and central field microperimetry.…”
Section: Introductionmentioning
confidence: 88%